ANALISIS MISKONSEPSI SISWA TERHADAP MATERI BIOLOGI SEMESTER GENAP KELAS VII DI MTs RIADHUL ULUM AMPENAN - Syamsuddin, Syamsuddin; Rozana, Umi Ulfa (Universitas Muhammadiyah Pontianak, 2023)
Misconceptions experienced by students is the lack of skills of students in translating sentences that are contextual into the concept contained in the book or reference. This study aims to analyze of student misconceptions about the concepts of energy on life, the interaction of living things with their environment, the impact of environmental pollution on life, and global warming and its impact on life, and to analyze factors that cause student misconceptions to biological concepts. The study included qualitative research, which describes the location of student misconceptions based on Certainty of Response Index (CRI) in solving multiple choice questions on the biology concept in Madrasah Tsanawiyah (MTs) of Riadhul Ulum Ampenan. The sample numbered 14 students as a subject. The data retrieval procedure was done by using the instrument in the form of multiplechoice diagnostic test to analyze the location of student misconception on every biological concept amounted to 24 questions. Data analysis has been done descriptively by exposing the type of answers, reason and CRI on each question. Most students have misconceptions about the concept of energy as the source of life. The concept of the interaction of living beings with their environment. The concept of the impact of environmental pollution on life. The concept of global warming and its impact on life. In addition, the source of students understanding comes from the books they read, and besides it can be sourced from friends, social media, teachers, and the student. CRI was developed to distinguish between students who had misconceptions, understood concepts and did not understand the concept.